Large Primary Tuberculous Psoas Abscess in an HIV Patient – A Case Report - Rakesh, TP; Kidangazhiathmana, A; Jyothish, K; Amrutha, PC; Satheeshbabu, TV (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2015)
Tuberculosis (TB) remains as one of the leading opportunistic infection in patients with Human immunodefficiency virus (HIV) infection in developing countries. Here we report a case of huge primary psoas abscess of tubercular origin in an HIV patient who presented with hip pain and limping. Psoas sign was evident on examination and CT scan of abdomen revealed a large iliopsoas abscess extending from abdomen to upper part of thigh. Patient underwent percutaneous drainage of abscess and improved with anti-tuberculous drugs while continuing anti-retroviral therapy. DOI: http://dx.doi.org/10.3126/saarctb.v11i2.12437 SAARC J TUBER LUNG DIS HIV/AIDS, 2014;XI(2), Page: 34-36